2016
DOI: 10.18632/oncotarget.8905
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin induced ROS results in abortive autophagy and leads to regulated necrosis in glioblastoma

Abstract: Glioblastoma is the most frequent malignant brain tumor. Even with aggressive treatment, prognosis for patients is poor. One characteristic of glioblastoma cells is its intrinsic resistance to apoptosis. Therefore, drugs that induce alternative cell deaths could be interesting to evaluate as alternative therapeutic candidates for glioblastoma. Salinomycin (SLM) was identified through a chemical screening as a promising anticancer drug, but its mechanism of cell death remains unclear. In the present work we set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 49 publications
4
51
1
Order By: Relevance
“…ER is a key organelle with protein processing, intracellular calcium storage, as well as signaling regulation functions in eukaryotic cells (31). Although the anticancer effects of salinomycin have been established in a variety of preclinical studies using many different cancer types, there are few studies on the effects of salinomycin on glioma cancer cells (6). In the present study, salinomycin showed potent cytotoxic and apoptotic effects in human glioma U87MG cells.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…ER is a key organelle with protein processing, intracellular calcium storage, as well as signaling regulation functions in eukaryotic cells (31). Although the anticancer effects of salinomycin have been established in a variety of preclinical studies using many different cancer types, there are few studies on the effects of salinomycin on glioma cancer cells (6). In the present study, salinomycin showed potent cytotoxic and apoptotic effects in human glioma U87MG cells.…”
Section: Discussionmentioning
confidence: 59%
“…Anticancer compounds may affect cellular redox reactions through accumulation of intracellular ROS (28,29), which in turn induce apoptosis and autophagy (30). Accumulating evidence indicates that apoptosis is also regulated by ER stress (6,21). ER is a key organelle with protein processing, intracellular calcium storage, as well as signaling regulation functions in eukaryotic cells (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, it has been reported that salinomycin, another polyether ionophore, can inhibit autophagic flux in hepatocellular carcinoma cells and breast cancer stem-like/progenitor cells (Klose, Stankov, Kleine, Ramackers, Panayotova-Dimitrova, Jager, Klempnauer, Winkler, Bektas, Behrens and Vondran 2014, Yue, Hamai, Tonelli, Bauvy, Nicolas, Tharinger, Codogno and Mehrpour 2013). Particularly, salinomycin has been found to suppress autophagic flux, triggering necrosis in glioblastoma cells (Xipell, Gonzalez-Huarriz, Martinez de Irujo, Garcia-Garzon, Lang, Jiang, Fueyo, Gomez-Manzano and Alonso 2016). Here, we found that maduramicin also blocked autophagic flux with accumulation of both LC3-II and p62/SQSTM1 (Fig.…”
Section: Discussionmentioning
confidence: 99%